Analisis Penelitian Ethnomathematics pada Siswa SMA di Dunia Pendidikan Internasional - Putri Kusuma, Ana Fatwa; Anggoro, Bambang Sri; Andriani, Siska (Jurnal Pendidikan Matematika : Judika Education, 2025)
This This study aims to explore the application of ethnomathematics in mathematics learning at the Senior High School (SMA) level in the context of international education. The method used is a Systematic Literature Review (SLR) by following the PRISMA guidelines for 22 articles published in the period 2015–2025 from the Scopus, ERIC, DOAJ, and Google Scholar databases. The results of the study indicate that the application of ethnomathematics based on local culture, such as batik, wayang, and traditional games, can improve students' understanding of mathematical concepts, motivation, and engagement. The use of technology, such as e-modules based on local culture and the flipped classroom model, has proven effective in enriching the learning experience. The conclusion of this study confirms that ethnomathematics has the potential to strengthen cultural identity while improving the quality of mathematics learning, with recommendations for improving teacher training and developing culture-based teaching materials on an ongoing basis.   Keyword: Ethnomathematics, Mathematics education, PRISMA, SLR, High school student